Is digital transformation a barrier to export reduction during COVID-19? The case of a developing country - Nguyen Cam Thuy; Luong Van Dat; Do Phu Dong; Vu Thuy Linh; Doan Ngoc Thang (Cogent Business & Management, 2023)
This paper investigates the impact of digital transformation on export reduction during COVID-19 by using unique data from Vietnamese manufacturing firms. Digital transformation reflects whether firms had already introduced digital technology before the COVID-19 outbreak or started using digital technology during the COVID-19 outbreak. Meanwhile, an export reduction is a partial de-internationalization in which firms decrease overseas sales. Estimation results from the instrumental variable probit method show that digital transformation has a negative effect on the probability of export reduction. This effect becomes particularly strong for micro, small and medium enterprises. Our findings have managerial implications for firm managers.
Keywords: 650; COVID-19; de-internationalization; developing countries; digital transformation; export reduction